2019
DOI: 10.14778/3352063.3352140
|View full text |Cite
|
Sign up to set email alerts
|

Adapting TPC-C benchmark to measure performance of multi-document transactions in MongoDB

Abstract: MongoDB is a popular distributed database that supports replication, horizontal partitioning (sharding), a flexible document schema and ACID guarantees on the document level. While it is generally grouped with "NoSQL" databases, Mon-goDB provides many features similar to those of traditional RDBMS such as secondary indexes, an ad hoc query language, support for complex aggregations, and new as of version 4.0 multi-statement, multi-document ACID transactions. We looked for a well understood OLTP workload benchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Alternative Data Schemas Database managers may model the relationships among data without database reference. There are two mainstream methods as presented in prior work [25]: (1) embedding all sub-documents into the parent document; (2) using a separate collection to record all relations among documents. We call them embedding and separating approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative Data Schemas Database managers may model the relationships among data without database reference. There are two mainstream methods as presented in prior work [25]: (1) embedding all sub-documents into the parent document; (2) using a separate collection to record all relations among documents. We call them embedding and separating approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Our evaluation includes three workloads: the Yahoo Cloud Serving Benchmark (YCSB) [37] v0.11, TPC-C [38], a popular OLTP benchmark adapted for NoSQL systems [39]; and an analytical processing workload modeled after the popular TPC-H [40] benchmark. In all cases the workload driver executes on a dedicated server.…”
Section: Discussionmentioning
confidence: 99%
“…We experimented with TPC-C [38], a popular online transaction processing benchmark emulating a commerce system with five types of transactions. While initially designed to test traditional RDBMS systems, we used a recent implementation that adapts it to match the NoSQL document data model and to test transactional features [39] The database is populated to simulate 500 warehouses resulting to 66 GB of data size (41.5 GB on disk space using compression). To have a continuous view of performance, we adapted the benchmark to report throughput and response time for each query every 2 seconds.…”
Section: Tpc-cmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite an immense variety of database benchmarks like TPC 1 for relational databases, YCSB [5] for key-value stores, and LDBC [7] for graph databases, several studies on document stores reported that existing benchmarks do not cover their specific workloads and data (e. g., TPC-C [12], YCSB [10]). Especially, the missing support of JSON arrays and nested objects led to several initiatives on the data generation side such as attempts that translate TPC-H data to JSON [15], and more recently, initial work on extending the well-known Wisconsin benchmark by a JSON data generator [11].…”
Section: Introductionmentioning
confidence: 99%